Study of the Effect of UV Radiation on the Impact Test of Epoxy-Polyurethane Blend Reinforced with Micro and Nano Silicon Carbide - T. Suhail, Ghasaq; H. Anter, Faik; Sh. Al- Sarraj, Ziyad (Al-Nahrain Journal of Science, 2025)
This research includes the use of epoxy and polyurethane resins to form a blend of Epoxy/Polyurethane with different ratios of (90–10)%, (80–20)%, (70–30)%, and (60–40)% to find the best ratio for impact strength as a function of material toughness; and strengthened with micro and nano silicon carbide at weight fractions of 2, 4, 6 and 8%. The impact test was studied in natural conditions and after exposure to UV irradiation for 24h. Results showed that the “polymer blend/nano silicon carbide” composite has better properties compared with the micro-silicon carbide-containing composite. The values of impact strength decrease with increasing the weight ratio for all samples. Values in the case of UV radiation are generally higher than values in natural conditions.